“Influencia de tres bioestimulantes aplicados al follaje sobre el rendimiento de la Lechuga “romana” (Lactuca sativa L.) en la zona de Puebloviejo”. - Alvario Ramírez, Alexis Gustavo (2018)
VIII. SUMMARY The present experimental work was carried out in the grounds of the Hacienda "La Keta", located via San Juan - Puebloviejo whose geographical coordinates are: longitude 790 54` 20” west, south latitude 010 54` 58” and altitude of 8 masl. The area has a humid tropical climate, according to the Holdribge classification, with an average annual temperature of 25.80 ° C, annual precipitation of 2203.8 mm, relative humidity of 79.6%, evaporation of 1738.7 mm. The soil is flat topography, clay-loam texture and regular drainage. Seed of "romana" lettuce was used as seed material. The treatments studied in the trial were the applications of gallinaza tea; Manure tea and vermicompost tea, each with three doses of 8.0; 10,0 and 15,0 L / ha plus an absolute control without biostimulant application, fractionated with two applications in the culture at 20 and 40 days after the transplant. The experimental design that was used was Complete Blocks Random with ten treatments and three repetitions. For the comparison and adjustments of treatment measures, the Duncan test was used at 95% probability. For the development of the experimental work were carried out the work of preparation of the nursery, preparation of the soil, delimitation of plots and blocks, transplant, fertilization, irrigation, weed control, hilling, phytosanitary controls and harvest. To estimate the effects of the treatments, we proceeded to take data on the percentage of seedlings, plant height, width and length of leaves, days to harvest, cabbage weight, yield and economic analysis. Based on the results obtained, it was determined that the biostimulants applied if they had an influence on the yield of lettuce in the area of Puebloviejo; the wormwood tea, in a dose of 8,0 L / ha, was the treatment that presented the highest percentage of seizure; the variables height of plant, width and length of the leaf excelled with the use of Tea of vermicompost as biostimulant applied to the crop; The treatments that were applied to vermicompost tea at all doses (8,0; 10,0 and 15,0 L / ha) were harvested in less time and the greater weight of the cabbage, yield and economic analysis was observed with the use of Vermicompost tea at a dose of 10.0 L / ha with a net benefit of $ 462.66. Key words: biostimulants, "Roman" lettuce, chicken manure tea, manure tea, vermicompost tea.